THE STUDENTS’ LEARNING STRATEGY AND MOTIVATION IN DEVELOPING THEIR SPEAKING ABILITY AT SIXTH SEMESTER OF ENGLISH DEPARTMENT (IAIN PAREPARE) - Dahlan, Era; Sunubi, Abd. Haris; Ahdar, Ahdar (Inspiring: English Education Journal, 2019)
The aim of this  research was to know  the Students learning startegy  and motivation in developing the students? speakin gability  at six thse mester of English department (IAIN   Parepare).The  researcher was applying at six thse mester of  English department (IAIN Parepare) through had escriptive qualitati veresearch. This research were using three kinds of instruments. The first instrument wastest, where the purpose of this instrument was to know the student tabilityin speaking. The                      second was interview, the aim of this instrument was to know   what strategy that the student use to develop their speaking.   The last was question naire, where this instrument was to know the motivation of the student in order   to    develop   their speaking.   After   analyzing the data from the question naire the research erfound that  students in the high andlow category have the same strong motivation in developing their speaking. However, interms of using strategy, the                             students in high category use more variated strategies than thelow category.  The   students in high category mostly   apply cognitive and metacognitive strategy while the students in   low   cataegory mostly used social strategy.